Peran Corporate Social Responsibility (CSR) dan Good Corporate Governance (GCG) Dalam Kinerja Keuangan Pada PT. Gresik Migas (Perseroda) (International Forum of Researchers and Lecturers, 2024)
This exploration utilizes a quantitative strategy to inspect the impact of Corporate Social Obligation (CSR) and Great Corporate Administration (GCG) on the monetary execution of PT. Gresik Migas (Perseroda). Essential information were gathered through polls appropriated to 40 workers of PT. Gresik Migas (Perseroda) utilizing purposive testing. Multiple linear regression was used as the analytical method. The outcomes demonstrate that CSR essentially impacts monetary execution, while GCG doesn't make a tremendous difference. The coefficient of assurance (R2) of 17.2% shows that CSR and GCG can make sense of a part of the fluctuation in monetary execution.